2011
DOI: 10.1007/s10344-011-0522-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Francisella tularensis in brown hare (Lepus europaeus) populations in Lower Saxony, Germany

Abstract: Francisella tularensis is the aetiological agent of tularemia. Hares, rabbits, and small rodents are the main hosts, but humans can be infected and develop severe clinical symptoms. In Germany, tularemia in humans was a rare disease during the last four decades, but since 2005, this zoonosis seems to be re-emerging. However, only very little is known about the prevalence in the host populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…Francisella specific PCR assays were positive in 23 hares and 1 rabbit which were further confirmed by cultivation of F. tularensis subsp. holarctica in 12 hares [18]. In the present study, cases of tularemia in hares in Germany from 2005 to 2010 were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Francisella specific PCR assays were positive in 23 hares and 1 rabbit which were further confirmed by cultivation of F. tularensis subsp. holarctica in 12 hares [18]. In the present study, cases of tularemia in hares in Germany from 2005 to 2010 were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Natural foci can be small, and Francisella cells are also known to survive in the environment without leading to outbreaks in human or animal populations (Sjö stedt 2007). Runge et al (2011) observed this phenomenon in a German region with a high prevalence of tularemia in hares where no human cases were reported. The results of the present study suggest a similar situation in other German regions.…”
Section: Tularemia Serology In Wild Animalsmentioning
confidence: 94%
“…European brown hares are the most affected animals, and contact with infected animals is the main source of infection in humans. Hares are highly susceptible to F. tularensis and usually die rapidly after infection (Mö rner and Sandstedt 1983, Mö rner et al 1988, Decors et al 2011, although a few chronic cases have been reported (Runge et al 2011, Hofer 2012. No seropositive hares could be found in the federal state of SchleswigHolstein, Germany (Frö lich et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these areas, cases often occur every year, and in higher numbers, than in less heavily affected endemic areas [91]. For example, areas of high endemicity have been identified in both Germany and Sweden [47,91]. In Sweden, the theory of nidality/ focality has been applied to the outbreaks of tularemia, where molecular typing of F. tularensis subsp.…”
Section: Eco-epidemiology Of Tularemiamentioning
confidence: 99%